Isolation and identification of Starmerella davenportii strain Do18 and its application in black tea beverage fermentation - Chuanhai Tu; Wenxiu Hu; Sijie Tang; Ling Meng; Zhihai Huang; Xiao Xu; Xiudong Xia; Fidelis Azi; Mingsheng Dong (Food Science and Human Wellness)
The objective of this study was to isolate and identify a yeast strain from the kombucha beverage and evaluate in-vitro its potential as a novel starter in beverage fermentation. Starmerella davenportii Do18 was characterized for its cholesterol reduction; growth at different conditions such as temperatures (25, 30, 37 and 42 °C), low pH (1.2, 1.5, 2.0 3.0, and 7.0), bile salts (0%, 0.25%, 0.5%, 1% and 2%) high-sucrose stress (2%, 10%, 20%, 40% and 60%); and in-vitro survival in gastric and intestinal environments. Results showed that the yeast strain has a cholesterol-lowering capacity of 45% ± 2%, grew at temperature of 37 °C and is resistant to pH 1.5, 2% bile and 40% sucrose solution, could survive in simulated gastric and intestinal environments. The physicochemical characteristics of the fermented beverages were also evaluated, which indicated that the yeast has pH reduction capacity and can produce organic acids and volatile compound such as 2-phenylethanol. Furthermore, the fermented beverage also has high total phenolics and flavonoids content and showed great antioxidant and antimicrobial activities. Therefore, the findings of this research provide strong evidence that S. davenportii Do18 has good fermentation properties, can be a potential starter in food and beverage fermentation.